The pilot and evaluation of a postnatal support Group for Iraqi Women in the year following the birth of their baby - Rooney, Rosanna; Kane, Robert; Wright, B.; Gent, V.; Di Ciano, T.; Mancini, Vincent (Frontiers Research Foundation, 2014)
The current study involved conducting a pilot test of a culturally sensitive support group program developed to assist Iraqi women in the year following the birth of their baby (CSSG-B) in Perth, Western Australia. The aim of this study was to evaluate the social validity of the program. It was hypothesized that women involved in the program would find the program to be socially valid and culturally appropriate, and will also report lower levels of depressive symptomatology and higher levels of social support, following the group intervention. Participants were 12 Iraqi Arabic speaking women, who had a child less than 12 months of age. The program was based on Iraqi women's explanatory models (Kleinman, 1978; Di Ciano et al., 2010) of the birth and motherhood experience. Social validity ratings were obtained during the implementation of the program in order to assess the level of acceptability of the intervention. A one-group pre-test-post-test design was used to determine if depressive symptoms had decreased during the course of the intervention and social support had increased. Results indicated that Iraqi Arabic speaking women found the support group intervention acceptable and relevant and there was a significant decrease in scores on the Edinburgh Postnatal Depression Scale (EPDS) from pre-test to post-test. These results that the culturally sensitive group intervention was culturally acceptable and was associated with decreased levels of depressive symptomatology.